LITERATURE STUDY ON TUBERCULOSIS ELIMINATION 2030: CHALLENGES AND INNOVATIONS IN INDONESIA - Agustin Widyowati; Predito Prihantoro (Indonesian Journal of Nutritional Epidemiology and Reproductive, 2026)
Indonesia occupies the second highest case burden in the world, so it faces a major challenge in reducing the death rate due to Tuberculosis (TB). This research aims to synthesize strategic barriers and map the most feasible innovations to accelerate the TB elimination target by 2030. This study used Systematic Review. This study used a Systematic Review. The search strategy was developed using Boolean operators with structured keywords, resulting in 185 articles spanning the period 2017-2026. These articles were re-identified using inclusion and exclusion criteria until 15 primary articles were obtained. Analyzed using the Thematic Analysis technique The analysis showed four main obstacles: catastrophic non-medical costs that trigger drug discontinuation, social stigma that hinders early detection, fragmentation of surveillance data, and uneven access to diagnostics. However, digital innovations such as AI and telemedicine offer new efficiencies in outbreak prediction and compliance monitoring. TB elimination requires a paradigm shift towards a holistic approach that integrates patient economic protection, national data synchronization, and adoption of Society 5.0 technology to permanently break the chain of transmission.